Early Feasibility Studies of Augmented Reality Navigation for Lateral Skull Base Surgery. Issue 7 (August 2020) - Creighton, Francis X.; Unberath, Mathias; Song, Tianyu; Zhao, Zhuokai; Armand, Mehran; Carey, John
Abstract : Hypothesis: An augmented reality (AR) platform using a head mounted display (HMD) can successfully display and register virtual computerized tomography (CT) data to corresponding real world anatomy using fiducial markers. Background: AR is a growing field in surgical planning, and has been used by this group to aide in orthopedic surgery applications. Intraoperative AR registration of preoperative CT images could improve identification of critical anatomical structures during lateral skull base surgery. Methods: An AR based HMD platform was created to allow for virtual display and real time manipulation of a temporal bone phantom model. Four fiducial markers were incorporated into this model and used to allow manual alignment of surface markers in real-time. To test the accuracy of this platform virtual lines were created in the AR environment running through the visualized real-world fiducial marker points. Target registration error (TRE) was calculated by measuring the orthogonal distance between these virtual lines and the corresponding virtual fiducial marker for each of the four markers from varying angles. Ten consecutive experiments were performed. Results: The AR based platform successfully displayed CT renderings in the AR environment and allowed real time translation and rotation for manual alignment. A TRE of 10.62 ± 5.90 mm was found. Conclusions: Our results suggest that AR visualization of CT imaging can be registered to patient surface landmarks, but current limitations of AR hardware resulted in TREs too large to be used in the lateral skull base. Future advancements in AR technology will hopefully allow for reduction of registration error.